Research elastic filler received by method of high-temperature shift crushing. - I. B. Kravchenko; A. E. Kornev; Y. A. Naumova; G. V. Nikolsky; I. A. Krasotkina (Тонкие химические технологии)
Possibility of using elastic filler which received of the waste of tyres by conditions of high temperatures and deformation is investigated in rubber technology. The presented part of work has been directed on studying of morphological properties elastic filler, abilities to participation in vulcanization process elastomer material, comparison given kind of filler with the products of recycling of the worn out tyres presented in the modern market.